The Implementation of Class Action As a Legal Effort for Mass Poisoning Victims in the Free Nutritional Meal Program - Rheyna Wisnu Puteri; Kaharuddin Kaharuddin (Green Publisher Indonesia, 2026)
The Free Nutritious Meal (Makan Bergizi Gratis or MBG) program, launched in early 2025 to combat malnutrition in Indonesia, has been marred by mass food poisoning affecting thousands of students due to bacterial contamination. This research examines negligence within the MBG management and the application of class action mechanisms as legal protection for victims. Using a normative legal method with a statutory approach, the study analyzes the Consumer Protection Law, the Indonesian Civil Code, and Supreme Court Regulation No. 1/2002. Findings indicate that beneficiaries hold legal standing as